The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12879-018-3258-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunogenic outer membrane proteins and evaluation of their protective efficacy against Stenotrophomonas maltophilia

Abstract: BackgroundStenotrophomonas maltophilia (S. maltophilia) is an emerging global multiple-drug-resistant organism. It becomes increasingly challenging to treat S. maltophilia infection effectively. Novel therapeutic and preventive approaches targeting S. maltophilia infection are still lacking. This study aims to isolate outer membrane proteins (Omps) from S. maltophilia and use immunoproteomic technology to identify potential vaccine candidates of Omps against S. maltophilia infections.MethodsOmps from S. maltop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In our preliminary study, we used immunoproteomic approach to discover that outer membrane protein A (OmpA) was a strong immunogenic antigen and could be a good vaccine candidate against S . maltophilia infection [19]. OmpA and OmpA-like proteins, such as OmpA in Escherichia coli ( E .…”
Section: Introductionmentioning
confidence: 99%
“…In our preliminary study, we used immunoproteomic approach to discover that outer membrane protein A (OmpA) was a strong immunogenic antigen and could be a good vaccine candidate against S . maltophilia infection [19]. OmpA and OmpA-like proteins, such as OmpA in Escherichia coli ( E .…”
Section: Introductionmentioning
confidence: 99%
“…V. anguillarum is a serious pathogenic bacteria in aquaculture that caused massive mortality of marine fish, bivalves, and crustaceans ( 55 , 56 ). More evidence proved that the outer membrane proteins of pathogenic bacteria are highly immunogenic and provide immune protection against pathogenic bacteria in fish as a vaccine ( 57 59 ). In our previous research, multiple immunogenic proteins have been identified in V. anguillarum including VirA, CheR, FlaC, OmpK, OmpR, Hsp33, VAA, Groel, OmpU, PteF, and SpK ( 60 , 61 ); the OmpK and OmpR as subunit vaccines induced the secretion of specific antibodies and immunoprotection with an RPS of 62.16% and 64.86%, respectively, against V. anguillarum .…”
Section: Discussionmentioning
confidence: 99%